Biodiversity of Three Backwaters in the South West Coast of India - Beslin Leena Grace (International Journal of Biodiversity, 2014)
For the conservation of biodiversity, it is not sufficient to preserve the living organisms or their gametes alone, because keeping fishes in aquaria or their gametes in freezers cannot conserve the full range of biodiversity which is due to the loss of the ecological complexity in their original habitats. For promoting richer biodiversity in the future, more complexity in biological communities is essential in their natural environments. In order to prevent depletion of biodiversity due to environmental alterations or other ways, it is necessary to understand how the diversity of life particularly at the species level is maintained and it is equally necessary to know how the terminal extinction of species takes place under natural conditions. Moreover, a database on fishery resources of the concerned environment is essential to make decision about specific programmes on conservation of fish germplasm resources. Hence, the present study aims to quantify the fish and shellfish resources of the selected backwaters such as Kadinamkulam, Veli, and Poonthura to know the real stocks present in such environment